Ruthenium(II)-catalyzed C3 arylation of 2-aroylbenzofurans with arylboronic acids/aryltrifluoroborates via carbonyl-directed C-H bond activation - Paymode, Dinesh J.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2015)
The Ru(II)-catalyzed carbonyl-directed C-H activation with (hetero)arylboron reagents has been executed for the synthesis of 2-aroyl-3-(hetero)arylbenzofurans. A hypothesis founded upon the involvement Of an active carbonatoruthenium(II) complex for a coordinative insertion and the aerobic oxidation of the in situ generated Ru(0) to Ru(II), to continue the catalytic cycle, has been extended.